GAYA BELAJAR TIPE ANAK INTROVERT DAN EKSTROVERT - Saiddaeni Saiddaeni (Lafadz Jaya Publisher, 2023)
This article aims to determine the learning style of type childrenintrovert andextrovert. Where is the childintrovert considered stupid for always avoiding social. Childextrovert who have good social status are considered smarter. In a dominated worldextrovert, child conditionintrovert less support. The problem is focused on directing the child's learning style according to his innate. Childintrovert need a quiet space and away from social to recharge its energy. Different fromextrovert filling his energy when socializing, talking with friends and a lively atmosphere. The method used in this article uses the literature method by searching for keywords in books and analyzing them with appropriate learning styles according to the character of each child. The variable studied in this study is the VAK learning style (visual, auditory, kinesthetic). All children have their own advantagesintrovert norextrovert. The results of this study that, innate characterintrovert andextrovert each has its own learning style and its advantages through understanding V-A-K theory and MBTI theory.